Water Production Rate in Comets - Deaza Rincon, Pedro Ignacio (Scientia et Technica, 2018)
In the atmosphere or coma of a comet, the dissociation of water gives the OH radical, that is detectable by radioastronomical methods. Analyzing the spectral emission line of 18 centimeters, corresponding to the hydroxyl OH, can be deduced its rate of production, and, consequently, is possible infer the rate of water production. The results of the measurements carried in France with the Nancay radio telescope, in Puerto Rico with the Arecibo Radio Telescope, in Hawaii with the J. C Maxwell telescope and in Chile with ALMA radiotelescope, are allowing currently trying to build unified models of evolution and activity cometary.